Reframing Education: Evaluating the Transformative Effects of the 2013 Curriculum - Nur Silfiatun Hasanah; Sumrotul Ilmiah (Universitas Nurul Jadid, 2024)
This research aims to analyze the impact of implementing the 2013 Curriculum, focusing on consistent implementation, evaluation of learning outcomes, acceptance by students and parents, and adaptation of teaching methods and continuous feedback. The research method involves direct observation and interviews with educators, students, parents, and school administrators to understand curriculum implementation and its impact comprehensively. The findings show that consistent curriculum implementation produces a structured learning experience while evaluating learning outcomes. Increases student academic performance. The positive reception from students and parents and adapting innovative teaching methods enrich the learning process. A system of feedback and continuous improvement ensures the relevance and effectiveness of the curriculum. The conclusion of this research confirms that implementing the 2013 Curriculum effectively supports the achievement of educational goals by improving the quality of learning and stakeholder involvement.